GENDER WAGE DISPARITY IN THE UNITED STATES: SOCIO-CULTURAL CONTEXT V. LEGISLATIONS - Agnes Nora Eko Wahyu Utami (Rubikon : Journal of Transnational American Studies, 2015)
This study aimed at investigating the contributing factors to the persistence of gender pay disparity in American workforce despite decades of the enactment of progressive, federal legislations concerning on women’s wage. This study employed sociological approach and utilized qualitative research to achieve its predetermined objectives. Utilizing library research, data were gathered and analyzed using gender theory, particularly the theory of devaluation of women’s work. The results of this study indicated that prevalent American cultural values on gender roles and pay secrecy interfere with the federal legislations concerning on women’s wage. Meaning to say, the socio-cultural context where the legislations are applied and enforced seems to be, in some ways, contradictory to the legislations. The data of this study showed that in the workplace, cultural values on gender roles affected the decisions in hiring and during the employment, which further resulted in gender discriminatory practices (in general) and gender wage discrimination (in specific). Meanwhile, the prevalence of cultural values of not talking about salary reinforced employer’s policy against salary disclosure (PSC rules), which led to the hindrance of wage transparency that is in fact, in contradictory to what the legislations suggested. As a conclusion, gender wage disparity could not be cured solely with the enactment of federal legislations. Evolutionary changes in cultural values of the society are also significant in eliminating the gender wage disparity in American workforce.Keywords: gender wage disparity, socio-cultural context, cultural values, federal legislations, pay secrecy